Cost‐analysis of persistent hyperkalaemia in non‐dialysis chronic kidney disease patients under nephrology care in Italy. Issue 5 (27th January 2020) - Provenzano, Michele; De Francesco, Maria; Iannazzo, Sergio; Garofalo, Carlo; Andreucci, Michele; Genualdo, Raffaele; Borrelli, Silvio; Minutolo, Roberto; Conte, Giuseppe; De Nicola, Luca
Abstract: Aim: In patients with chronic kidney disease (CKD), hyperkalaemia (HK) (potassium level ≥ 5.0 mEq/L) is associated with poor clinical outcomes. This study provides novel insights by comparing management costs of CKD patients with normokalaemia vs those with persistent HK regularly followed in renal clinics in Italy. Methods: To this aim, a Markov model over life‐time horizon was developed. Time to end‐stage renal disease (ESRD) and time to death in CKD patients were derived from an observational multi‐centre database including 1665 patients with non‐dialysis CKD stage 1‐5 under nephrology care in Italy (15 years follow‐up). Resource use for CKD and HK management was obtained from the observational database, KDIGO international guidelines, and clinical expert opinion. Results: Results showed that patients with normokalaemia vs persistent HK brought an average per patient lifetime cost‐saving of €16 059 besides delayed onset of ESRD by 2.29 years and increased survival by 1.79 years with increment in total survival and dialysis‐free survival in normokalaemia that decreased from early to advanced disease. Cost‐saving related to normokalaemia increased at more advanced CKD; however, it was already evident at early stage (3388.97€ at stage 1‐3a). OWSA confirmed cost‐saving associated with normokalaemia across all parameter variations. Discussion and conclusion: This model is the first to simulate the impact of HK in non‐dialysis CKD patients on economic and clinical outcomes using real‐world data from nephrology clinics. In these patients, persistent HK results into higher lifetime costs, besides poorer clinical outcomes, that are evident since the early stages of CKD. Maintaining normokalaemia should therefore be of main concern in CKD treatment planning to improve long‐term economic and clinical outcomes.